Von Hippel–Lindau disease-associated renal cell carcinoma: a call to action. Issue 1 (January 2022) - Larcher, Alessandro; Rowe, Isaline; Belladelli, Federico; Fallara, Giuseppe; Raggi, Daniele; Necchi, Andrea; Montorsi, Francesco; Capitanio, Umberto; Salonia, Andrea
Abstract : Purpose of review: While the molecular and genetic bases of Von Hippel–Lindau (VHL) disease have been extensively investigated, limited evidence is available to guide diagnosis, local or systemic therapy, and follow-up. The aim of the current review is to summarize the ongoing trials both in preclinical and clinical setting regarding VHL disease management. Recent findings: Although genotype/phenotype correlations have been described, there is considerable inter and intra-familiar heterogeneity in VHL disease. Genetic anticipation has been reported in VHL disease. From a clinical point of view, expert-opinion-based protocols suggest testing those patients with any blood relative of an individual diagnosed with VHL disease, those with at least 1 or more suggestive neoplasms or patients presenting with clear cell renal cell carcinoma (ccRCC) diagnosed at a less than 40 years old, and/or multiple ccRCC. Clinical research is focused on safety and efficacy of systemic agents for patients with VHL-related ccRCC, with the aim to possibly preserve kidney function and improve patient survival. Summary: To date, preclinical and clinical research on the topic is scarce and clinical guidelines are not supported by strong validation studies.